Decortication in Chronic Pleural Empyema and Its Effect on Lung Function in Pediatric patients - Yadav, Ramdhani; Hasan, Zaheer; Kumar Thakur, Vinit; Prasad, Ramjee (Journal of Neonatal Surgery, 2025)
Background: Chronic pleural empyema, a condition marked by ongoing pleural infection and the development of a fibrous sheath around the lungs, severely impacts lung function and overall well-being in pediatric patients. Decortication is a surgical procedure aimed at removing this fibrous layer to restore normal lung mechanics. This study investigates the impact of decortication surgery on lung function in children with chronic pleural empyema and evaluates how factors such as malnutrition, obesity, and cardiovascular conditions influence surgical outcomes. Methods: This prospective cohort study included 80 children aged 5 to 15 years diagnosed with chronic pleural empyema who underwent decortication. Clinical and demographic data, including age, sex, nutritional status, and comorbidities, were collected. Lung function was evaluated through spirometry before and after surgery, focusing on parameters such as FEV1 and FVC. Postoperative complications, including bleeding, infections, and air leaks, were recorded along with hospital stay duration. Paired t-tests assessed changes in lung function, while subgroup analyses explored the effects of malnutrition and other comorbidities on recovery. Results: The participants had an average age of 10.2 ± 2.8 years, with males accounting for 60% of the cohort. Post-surgical lung function showed significant improvement, with FEV1 rising from 1.2 ± 0.3 L to 1.7 ± 0.4 L (p < 0.001) and FVC increasing from 1.6 ± 0.4 L to 2.3 ± 0.5 L (p < 0.001). Common complications included bleeding (10%), infections (12%), and prolonged air leaks (15%). Malnutrition was associated with slower recovery and a higher rate of complications. The average hospital stay was 10 ± 3 days. Conclusion: Decortication is highly effective in improving lung function in children with chronic pleural empyema. Even in patients with malnutrition and comorbidities, this intervention demonstrates significant benefits. These findings underscore the value of timely surgery and individualized perioperative care in improving outcomes for this vulnerable group.